2011
DOI: 10.3797/scipharm.1107-19
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Cytotoxic Natural Product DNA Intercalating Agents by Caffeine

Abstract: Many anti-tumor drugs function by intercalating into DNA. The xanthine alkaloid caffeine can also intercalate into DNA as well as form π-π molecular complexes with other planar alkaloids and anti-tumor drugs. The presence of caffeine could interfere with the intercalating anti-tumor drug by forming π-π molecular complexes with the drug, thereby blocking the planar aromatic drugs from intercalating into the DNA and ultimately lowering the toxicity of the drug to the cancer cells. The cytotoxic activities of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 51 publications
(61 reference statements)
1
36
0
Order By: Relevance
“…By contrast, Hill et al (13) reported that caffeine may attenuate the cytotoxic effect of intercalating antitumor drugs, such as doxorubicin. That study described a possible interceptor role of caffeine, protecting cancer cell DNA from intercalation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Hill et al (13) reported that caffeine may attenuate the cytotoxic effect of intercalating antitumor drugs, such as doxorubicin. That study described a possible interceptor role of caffeine, protecting cancer cell DNA from intercalation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of caffeine is more controversial (12). A previous study suggested that caffeine may attenuate the MCF-7 cell response to chemotherapy due its ability to intercalate into DNA (13). By contrast, another study performed on MCF-7 breast cancer cells treated with paclitaxel reported that caffeine supplementation enhanced the apoptosis induction triggered by the chemotherapeutic drug (14).…”
Section: Introductionmentioning
confidence: 91%
“…Hetero-association in Drug-xanthine systems has been extensively studied by NMR, UV-vis, Fluorescence spectroscopies, titration microcalorimetry, partitioning in waterorganic mixture, molecular modelling and other techniques for the following aromatic drugs: daunomycin (DAU) [127,[133][134][135][136], doxorubicin (DOX) [33,42,127,[137][138][139], actinomycin D (AMD) and its derivatives [133,[140][141][142][143], benzene and its derivatives [122,144], novantrone/mitoxantrone (NOV) [42, 127, 135-137, 145, 146], nogalamycin (NOG) [138], norfloxacin (NOR) [135,136,147], camptothecins [139,148,149], quinoxaline [84], chloroquine [84], DAPI [150], phenothiazines [121,151,152], riboflavin [135,[153][154][155], porphyrins [156,157], acridine mutagens [53,54,124,125,[133][134]…”
Section: Drug-xanthine Systemmentioning
confidence: 99%
“…the longitudinal axes of the chromophores of the drug and xanthine molecules tend to be parallel) [42,124,125,133,135,137,139,159], except for the cases of THP-NOV [135] and, probably, CAF-DOX [139] systems in which the longitudinal axes are nearly orthogonal (the CAF-DOX seems to be the only system for which the early [42,137] and recent [139] calculations of the structure of 1:1 hetero-complex disagree with respect to the angle of orientation of CAF to the DOX chromophore). The key difficulty in structural modelling of drug-xanthine systems is that the xanthine molecule allows at least two possible orientations differing by 180º in the complex with the drug [133,137,139], which sometimes cannot be reliably discriminated by experiment or in structural modelling. In the majority of cases, a typical aromatic stacking distance of 0.33-0.35 nm between the chromophores of the molecules in 1:1 complexes was reported.…”
Section: Drug-xanthine Systemmentioning
confidence: 99%
“…This mechanism of protection is known as "interceptor" mode of CAF and other methylxanthines action and was proposed by Bedner et al [19]. The "interceptor" mode of CAF was described and analyzed for HCAs [15] and several other aromatic compounds: ethidium bromide [20,21], propidium iodide [19,20], quinacrine mustard, ICR170, ICR191 [22], proflavine [23], and several anticancer drugs [17,24,25]. Similar mechanism was also described for interaction of chlorophyllin (CHL) [26] and other natural constituents of human diet [27] with several aromatic compounds.…”
Section: Mechanism Of Heterocomplexationmentioning
confidence: 99%